Triple semicircular canal occlusion with endolymphatic sac decompression for intractable Meniere’s disease - Tian, Jiawang; Yin, Gendi; Zhang, Qian; Zhang, Shuqi; Zeng, Xiangli; Li, Yongqi (Frontiers in Neurology, 2024)
Background: Meniere's disease (MD) is characterized by idiopathic endolymphatic hydrops (ELH).Frequent vertigo attacks is the most disabling symptom of MD. Objective: This study evaluated the efficacy of triple semicircular canal occlusion combined with endolymphatic sac decompression in the treatment of frequent vertigo in patients with MD. Methods: Eleven patients with complete medical records were included in this study conducted from May 2021 to April 2022. All patients were enrolled to undergo triple semicircular canal occlusion (TSCO) with endolymphatic sac decompression (ESD). Various tests including pure tone audiometry (PTA), vestibular evoked myogenic potentials (VEMPs), the video head impulse test (v-HIT), caloric test data, the Dizziness Handicap Inventory (DHI), the Berg Balance Scale (BBS), and the Tinnitus Handicap Inventory (THI) were performed both before and after the surgery. Results: The successful control rate of vertigo was 100% (9/9) in the average 23-month postoperative follow-up period, with complete control rate of 88.89% (8/9) and substantial control rate of 11.11%(1/9). Conclusion: TSCO combined with ESD may be an effective treatment option for managing frequent vertigo attacks in patients with MD. This combination therapy has the potential to become a significant addition to the treatment framework for MD.